2008
DOI: 10.1253/circj.72.384
|View full text |Cite
|
Sign up to set email alerts
|

Activation Patterns and Conduction Velocity in Posterolateral Right Atrium During Typical Atrial Flutter Using an Electroanatomic Mapping System

Abstract: Background To investigate the activation patterns and conduction velocity (CV) in the posterolateral right atrial (RA) wall during typical counterclockwise atrial flutter (AFL) using an electroanatomic mapping system. Methods and Results During typical AFL in 25 patients, the transverse conduction pattern and CV were classified and calculated. The line blocking transverse conduction was defined by the conduction pattern and double potentials recorded during mapping. There were 3 types (including 2 subtypes) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
3
10
0
Order By: Relevance
“…Several studies reported that the CTI was a region of slowing of conduction using either conventional mapping or classical 3‐D electroanatomical mapping system . In another study using the CARTO system in 25 patients, Sawa et al could measure a CV of 0.59 ± 0.21 m/s within the CTI, which is in total agreement with our data (0.56 ± 0.18 m/s) …”
Section: Discussionsupporting
confidence: 93%
“…Several studies reported that the CTI was a region of slowing of conduction using either conventional mapping or classical 3‐D electroanatomical mapping system . In another study using the CARTO system in 25 patients, Sawa et al could measure a CV of 0.59 ± 0.21 m/s within the CTI, which is in total agreement with our data (0.56 ± 0.18 m/s) …”
Section: Discussionsupporting
confidence: 93%
“…A) and the mean CV for the whole circuit was 0.805 m/sec. These CVs were equivalent to the CV in the normal atrial tissue (0.3–1.0 m/sec) and similar to reported previously . With such a limitation in the method of determining the local CV, we found a highly significant linear correlation between the local CV and lnEA, and proposed formula 2 to estimate the local CV.…”
Section: Discussionsupporting
confidence: 87%
“…36,37 In the non-contact mapping study by Tai et al, 36 the line of block in the SV was observed during atrial pacing even at a long CL (500 ms) in the majority of AFL patients, whereas more rapid pacing was required for it to develop in some patients, suggesting that the structural (anatomical) properties of the SV play a dominant role in the formation of the line of block, but that additional functional factors are also involved in a certain population of patients. In the present study, there were no significant differences between the control and AFL patients in the rate-dependent or dynamic properties of the MAP in the SV, except for a slight prolongation of the MAPD90 at the shortest CL examined (300 ms) in the AFL group.…”
Section: Discussionmentioning
confidence: 99%